Prevalence of Foreign Bodies in the Rumen and Reticulum of goat at Hama municipal slaughterhouse (Journal of Hama University, 2022)
A study was conducted from December, /2017/ to December, /2018/ in Hama municipal slaughterhouse, with the objectives of to assess the prevalence of foreign bodies in rumen and reticulum, identifying types of foreign bodies and associated risk factors for the occurrence of indigestion with foreign bodies.A gross examination of the rumen and reticulum contents of goat carcasses was conducted in the municipal slaughterhouse in Hama to investigate the presence of foreign bodies that were removed and to calculate the prevalence rate, which amounted to 30% of the examined carcasses, which numbered (1300n =), (845 male and 455 female), 30%(n=390) were found affected with foreign bodies at slaughter. When the prevalence was compared between sex, among different age groups, among different body condition score (BCS), season, higher percent prevalence of foreign bodies 39.56%, 72.53%,70.87%, 49.21% were observed in female, aged more than 4 years, animal having poor body condition score BCS , in winter season, respectively. These aforementioned factors are considered as potential risk factors and found highly significantly associated (p < 0.05) with the occurrence of foreign bodies. Rumen harbored mostly plastic materials while rumen and reticulum were the major site for the retention of metallic objects. This study shows that the presence of foreign bodies in the rumen and reticulum  plays a role in pathogenesis, low production, and increases the mortality rate.